Education on Maintaining Food Hygiene as an Effort to Prevent Disease Transmission - Yanabila Annisatity; Dwi Warna Aju Fatmawati; Benni Benyamin; Agustin Wulan Suci Dharmayanti (ABDIGI : JURNAL PENGABDIAN MASYARAKAT KESEHATAN GIGI, 2023)
Foodborne disease is caused by various biological contaminants from food contamination caused by worms, parasites, bacteria, fungi and viruses. The spread of various diseases is often known to be related to food hygiene and sanitation, thus triggering poisoning, allergies, diarrhoea, hepatitis A and even COVID-19. Community service activities aim to accompany community behaviour and food hygiene in the midst of the new normal era at BUMDES Griya Kuliner Pacet. Community service activities were carried out for 30 days at Griya Culinary, Pacet Village, Mojokerto, East Java. The method used in this activity is the assistance of the head of the Culinary House management and several traders. In order to maximize the mentoring process, the community service team conducted surveys up to the evaluation stage. Before the service team provided this, respondents' knowledge and methods of hygienic food processing still needed to be improved. However, after education regarding hygienic food processing was carried out, respondents' knowledge increased. Results were achieved through Community Service activities regarding safe, clean and healthy food processing and serving methods, as well as the availability of health promotion media in the form of leafletKeyword : community empowerment; education; foodborne; food hygiene